miR-7 suppresses brain metastasis of breast cancer stem-like cells by modulating KLF4 - Okuda, Hiroshi (2013)
Despite significant improvement in survival rates of breast cancer patients, prognosis of metastatic disease is still dismal. Cancer stem-like cells (CSCs) are considered to play a role in metastatic progression of breast cancer; however, the exact pathological role of CSCs is yet to be elucidated. In this report, we found that CSCs (CD24(−)/CD44(+)/ESA(+)) isolated from metastatic breast cell lines are significantly more metastatic than non-CSC populations in an organ specific manner. The results of our microRNA profile analysis for these cells revealed that CSCs that are highly metastatic to bone and brain expressed significantly lower level of miR-7 and that this microRNA was capable of modulating one of the essential genes for induced pluripotent stem cell, KLF4. Interestingly, high expression of KLF4 was significantly and inversely correlated to brain- but not bone-metastasis free survival of breast cancer patients, and we indeed found that the expression of miR-7 significantly suppressed the ability of CSCs to metastasize to brain but not to bone in our animal model. We also examined the expression of miR-7 and KLF4 in brain-metastatic lesions and found that these genes were significantly down- or up-regulated, respectively, in the tumor cells in brain. Furthermore, the results of our in vitro experiments indicate that miR-7 attenuates the abilities of invasion and self-renewal of CSCs by modulating KLF4 expression. These results suggest that miR-7 and KLF4 may serve as biomarkers or therapeutic targets for brain metastasis of breast cancer.